Mechanistic DNA damage simulations in Geant4-DNA Part 2: Electron and proton damage in a bacterial cell. (April 2018) - Lampe, Nathanael; Karamitros, Mathieu; Breton, Vincent; Brown, Jeremy M.C.; Sakata, Dousatsu; Sarramia, David; Incerti, Sébastien
Highlights: Using Geant4-DNA, we simulate DNA damage yields in a bacterial DNA. Damage yields from electrons and protons are presented. The strand break yield from the natural radiation background is calculated. We hypothesize that natural radiation only minimally contributes to mutations. Abstract: We extended a generic Geant4 application for mechanistic DNA damage simulations to an Escherichia coli cell geometry, finding electron damage yields and proton damage yields largely in line with experimental results. Depending on the simulation of radical scavenging, electrons double strand breaks (DSBs) yields range from 0.004 to 0.010 DSB Gy −1 Mbp −1, while protons have yields ranging from 0.004 DSB Gy −1 Mbp −1 at low LETs and with strict assumptions concerning scavenging, up to 0.020 DSB Gy −1 Mbp −1 at high LETs and when scavenging is weakest. Mechanistic DNA damage simulations can provide important limits on the extent to which physical processes can impact biology in low background experiments. We demonstrate the utility of these studies for low dose radiation biology calculating that in E. coli, the median rate at which the radiation background induces double strand breaks is 2.8 × 10 −8 DSB day −1, significantly less than the mutation rate per generation measured in E. coli, which is on the order of 10 −3 .